Penyuluhan Hukum Perlindungan Hak Petani Terhadap Pengembangan Varietas Tanaman Lokal Di Negeri Layeni Dan Negeri Wotay Kabupaten Maluku Tengah - Ronald Saija; Muchtar Anshary Hamid Labetubun; Michael Nussy; Jimris F Nikodemus (AIWADTHU: Jurnal Pengabdian Hukum, 2021)
Introduction: The use of resources in a directed and efficient manner requires complete availability of data and information regarding climatic conditions, soil and other physical environmental characteristics, as well as requirements for cultivated plants, especially plants that have sufficient market opportunities and economic meaning. The development of plantation commodities in Central Maluku Regency, Teon Nila Serua District, especially Negeri (Village) Layeni and Negeri Wotay is slower than the potential available land.Purposes of Devotion: Providing an understanding of the protection of traditional crop varieties for the rights of farmers, especially farmers in Negeri Layeni  and Negeri Wotay, Central Maluku RegencyMethod of Devotion: Performed with the lecture method by each of the presenters. The lecturer is given time to deliver the material, after which the participants are invited to ask a problem or question, which is then answered in turn by the speaker according to the problem being asked.Results of the Devotion: Efforts to increase productivity are strongly influenced by success in improving the genetic potential of plant varieties. Activities that can produce more superior plant varieties need to be encouraged by providing incentives for people or business entities engaged in plant breeding that produce new varieties so as to provide greater added value to users. The strategy for developing superior plantation commodities must be implemented based on the principles of benefit and sustainability and integration. Plantation development in Central Maluku Regency must be based on land potential.